Handbook of fiber optic data communication - DeCusatis, Casimer (San Diego, CA : Academic Press, 2002)
The Handbook includes chapters on all the major industry standards, quick reference tables, helpful appendices, plus a new glossary and list of acronyms. This practical handbook can stand alone or as a companion volume to DeCusatis: Fiber Optic Data Communication: Technological Advances and Trends (February 2002, ISBN: 0-12-207892-6), which was developed in tandem with this book. * Includes emerging technologies such as Infiniband, 10 Gigabit Ethernet, and MPLS Optical Switching * Describes leading edge commercial products, including LEAF and MetroCore fibers, dense wavelength multiplexing, and Small Form Factor transceiver packages * Covers all major industry standards, often written by the same people who designed the standards themselves * Includes an expanded listing of references on the World Wide Web, plus hard-to-find references for international, homologation, and type approval requirements * Convenient tables of key optical datacom parameters and glossary with hundreds of definitions and acronyms * Industry buzzwords explained, including SAN, NAS, and MAN networking * Datacom market analysis and future projections from industry leading forecasters.
Optical fiber, cable, and connectors -- Optical sources : light-emitting diodes and laser technology -- Detectors for fiber optics -- Logic and drive circuitry -- Optical subassemblies -- Fiber optic transceivers -- Fiber optic link requirements -- Planning and building the optical link -- Testing fiber optic local area networks (LANs) -- Introduction to Industry Standards -- Intramachine communications -- Applications : Asynchronous Transfer mode and synchronous optical network -- Fibre channel standard -- Enterprise systems connection fiber optic link -- Local area networks, fiber distributed data interface, ethernet, and token ring -- Semiconductor laser and light-emitting diode fabrication -- Receiver, laser driver, and phase-locked loop design issues -- Packaging assembly techniques -- Alignment metrology and techniques.
Includes bibliographical references and index.
Keywords: Optical communications; Fiber optics; Data transmission systems; Optical communications. Fiber optics. Data transmission systems; Electrical engineering; Engineering; Electronic books